EFEKTIFITAS FOTOTERAPI 24 JAM DAN 36 JAM TERHADAP PENURUNAN BILIRUBIN INDIRECT PADA BAYI IKTERUS NEONATORUM - harlina yuhanidz; saryono -; giyatmo - (Jurnal Ilmiah Kesehatan Keperawatan, 2011)
One of therapy to reduce the indirect bilirubin level is to use fototherapy. There are several methods to provide a phototherapy, that conducted for 24 hour and 36 hour of phototherapy. This study aimed to identify the differences in the effectiveness of phototherapy 24 hour and 36 hour to the indirect bilirubin level in icterus neonatorum  patient of  PKU Muhammadiyah Hospital Gombong . This research was a quasi-experimental study, Non randomized pre test-post test with control design. The population in this study were all patients who were treated at PKU Muhammadiyah. The amaunt of sample were 50 patient.Data was analyzed by paired t-test and independent t-test. Statistical analysis with independent t-test showed that the t value > t table  (2,741 >1.71), its mean there was a difference between phototherapy 24 hour and 36 hour significantly to indirect bilirubin level in icterus neonatorum patient at RSU PKU Muhammadiyah  Gombong. The 36th hour of phototherapy was more efectifity to reduce indirect billirubin level in icterus neonatorum patient.   Keywords: 36 hour , 24 haur, phototherapy, efectivity.